Studi komparasi beberapa metode skrining penilaian status gizi pada pasien dewasa rawat inap rumah sakit - Rizki Andini; Susetyowati Susetyowati; Dian Caturini Sulistyoningrum (Jurnal Gizi Klinik Indonesia, 2017)
Background: It is necessary to diagnose level of malnutrition in hospitalized patient to give optimal nutrition support. Many different nutrition screening assessment have been developed. In Indonesia, Simple Nutrition Screening Tool (SNST) that had been used in same hospital and the result was good enough in validity-realibility.Objective: To assessed that SNST were simple and practical nutrition screening tool for detecting level of malnutrition in different type of hospitalized patient.Method: Observational cross-sectional design with total of sampling two hundred and eighty seven adult patients from 2nd and 3rd class of surgical, internal, or neurology ward of RSUD Sleman. Independent variables are SNST, Nutritional Risk Screening (NRS) 2002, Malnutrition Screening Tool (MST), and Malnutrition Universal Screening Tool (MUST). Dependent variables are Subjective Global Assessment (SGA), body mass index (BMI), mid upper arm circumference (MUAC), and hemoglobin (Hb). Receive Operating Curve (ROC) were used for measuring validity of each screening tools. The proportion difference between at-risk group and not at-risk group was assessed by Chi-square test. The mean difference of BMI, MUAC, and Hb between both of group was assessed by independent sample t-test.Results: SNST has highest validity compared to NRS-2002, MST, and MUST with Sensitivity 99,0%, Specificity 84,5 and Area Under Curve (AUC) 0,917. Based on SNST, the proportion difference of at-risk group and not at-risk group between surgical patients and internal-neurology patients was statistically significant (p<0,05); the proportion difference of at-risk group and not at-risk group between young adult, adult, and elderly patients was statistically significant (p<0,05); the mean difference of BMI, MUAC, and Hb between at-risk group and not at-risk group was also statistically significant (p<0,05).Conclusion: All of the nutrition screening tools can be used as predictor of malnutrition in hospitalized patients but, the SNST has the best validity as a nutrition screening to predict malnutrition.